AVS-M Audio: Algorithm and Implementation. (13th January 2011) - Zhang Zhang, Tao Tao; Liu Liu, Chang-Tao Chang-Tao; Quan Quan, Hao-Jun Hao-Jun
Abstract : In recent years, AVS-M audio standard targeting at wireless network and mobile multimedia applications has been developed by China Audio and Video Coding Standard Workgroup. AVS-M demonstrates a similar framework with AMR-WB+. This paper analyses the whole framework and the core algorithms of AVS-M with an emphasis on the implementation of the real-time encoder and decoder on DSP platform. A comparison between the performances of AVS-M and AMR-WB+ is also given.